Meet Trouble Pre-Level 1, Ages 4-6 - Hood, Susan; Stephenson, Kristina (New York , Grosset and Dunlap - Penguin Group, 2001)
Double the trouble - two stories in one book! Meet Trouble: an adorable kitten - who gets in trouble! Double Trouble. Who is that kitten? Trouble will find out!
Keywords: English Fiction